1988
DOI: 10.1017/s0266462300004062
|View full text |Cite
|
Sign up to set email alerts
|

Health Technology Development in Japan

Abstract: This article provides a comprehensive analysis of the social, cultural and economic factors which have led to the present pattern of technology utilization in Japan. It is divided into five sections. The first provides the historical framework; the second, an overview of the health care delivery context and its economic incentive structure; the third, an analysis of the various contenders involved in the process of resource allocation; the fourth, a description of the technology areas which have been emphasize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

1989
1989
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 10 publications
(5 reference statements)
0
8
0
1
Order By: Relevance
“…Empirical studies on US [14,15] and Japanese hospitals [16] have shown that low prospective payment rates negatively affect the adoption of technologies, particularly cost-increasing ones, though the extent of this varies from case to case. In addition, a positive association between the degree of competition in the health care market and the propensity to adopt new technologies has been reported [17].…”
Section: Medical Technology Diffusion and Measurement Issuesmentioning
confidence: 99%
“…Empirical studies on US [14,15] and Japanese hospitals [16] have shown that low prospective payment rates negatively affect the adoption of technologies, particularly cost-increasing ones, though the extent of this varies from case to case. In addition, a positive association between the degree of competition in the health care market and the propensity to adopt new technologies has been reported [17].…”
Section: Medical Technology Diffusion and Measurement Issuesmentioning
confidence: 99%
“…The financing structure is described in more detail elsewhere (e.g., Ikegami, 1988;Ikegami et al, 1994;Ikegami and Campbell, 1995;1996;Oliver et al, 1997), but its salient features are that it is a fee-for-service system based on a tightly controlled fee schedule, where across the board reductions in fees -irrespective of an intervention's effectiveness or value for money -are regularly imposed by the government. The ways in which the system of health care financing, together with other factors, serve to restrict the incentives for the government, purchasers, providers, manufacturers and universities to commission and/or undertake economic evaluation, will now be detailed.…”
Section: The Disincentives For Undertaking Economic Evaluationmentioning
confidence: 99%
“…Screening practices and the installation of diagnostic equipment may be relatively common because of the revenue that can be derived from voluminous diagnostic testing, and/or because the hospital administrators feel that investing in the latest diagnostic equipment is effective in attracting both patients and doctors. Alternatively, the popularity of screening and diagnostics could be based on a cultural preference for non-invasive techniques (Ikegami, 1988;Hisashige, 1997). The above factors may explain why screening, diagnostic procedures and cancer appear to be the foci of interest with respect to economic evaluation.…”
Section: Universitiesmentioning
confidence: 99%
“…As a result, the health care demands of the essentially healthy general population have been well taken care of without excessive allocation of resources to high technology medicine. The end results appear to have been highly successful: Japan has one of the lowest infant mortality rates and the longest life expectancy in the world while the proportion of the GNP devoted to health has remained at a level of around 5% (Ikegami, 1988). Elaborating on Definition B, as it applies to Japan, the preferred medical practice in Japan could be summarized as follows: 'immediate, tangible and non-invasive response to the perceived medical problem'.…”
Section: Japan's Situationmentioning
confidence: 99%
“…Thus, it can be inferred that while the high examination rate may have led to a high consumption of pharmaceuticals, it has not resulted in aggressive treatment by surgery. This preference for 'non-invasive' technology is evident not only among the doctors, but also in the manufacturers of appliances; while various forms of diagnostic equipment such as CT scanners are produced and exported in large number, equipment which requires an invasive operation such as pace-makers and artificial heart valves are almost wholly imported (Ikegami, 1988).…”
Section: Naoki Ikegamimentioning
confidence: 99%